The origins of the final solution : the evolution of Nazi Jewish policy, September 1939 - March 1942 - Browning, Christopher R. 1944- (Comprehensive history of the Holocaust, 2004)
In 1939, the Nazi regime's plans for redrawing the demographic map of Eastern Europe entailed the expulsion of millions of Jews. By the fall of 1941, these plans had shifted from expulsion to systematic and total mass murder of all Jews within the Nazi grasp. This book is the most detailed and comprehensive analysis ever written of what took place during this crucial period--of how, precisely, the Nazis' racial policies evolved from persecution and "ethnic cleansing" to the Final Solution of the Holocaust. Meticulously documenting the process that led to this fatal development, Browning shows that Adolf Hitler was the key decision-maker throughout, approving major escalations in Nazi persecution of the Jews at victory-induced moments of euphoria